2018
DOI: 10.1074/jbc.m117.809608
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome sequencing reveals that cell division cycle 5-like protein is essential for porcine oocyte maturation

Abstract: The brilliant cresyl blue (BCB) test is used in both basic biological research and assisted reproduction to identify oocytes likely to be developmentally competent. However, the underlying molecular mechanism targeted by the BCB test is still unclear. To explore this question, we first confirmed that BCB-positive porcine oocytes had higher rates of meiotic maturation, better rates of cleavage and development into blastocysts, and lower death rates. Subsequent single-cell transcriptome sequencing on porcine ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 71 publications
2
26
2
Order By: Relevance
“…Furthermore, we observed that nuclear maturation (MII) did not differ between BCB+ and BCBoocytes from the mixed, large, and small diameter groups. These results (MII) do not support previous studies, where it was shown that BCB+ oocytes are more competent to complete MII (ALM et al, 2005;LIU et al, 2018;RODRIGUEZ-GONZALEZ et al, 2002). Although our results on maturation (MII) did not differ between the BCB+ and BCB-oocytes within the same follicular group, there were marked differences between the follicular groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we observed that nuclear maturation (MII) did not differ between BCB+ and BCBoocytes from the mixed, large, and small diameter groups. These results (MII) do not support previous studies, where it was shown that BCB+ oocytes are more competent to complete MII (ALM et al, 2005;LIU et al, 2018;RODRIGUEZ-GONZALEZ et al, 2002). Although our results on maturation (MII) did not differ between the BCB+ and BCB-oocytes within the same follicular group, there were marked differences between the follicular groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Oocyte competence is progressively acquired towards the end of folliculogenesis, when many cellular and molecular changes occur (ADONA et al, 2016;LIU et al, 2018). Such changes can influence various components of maturation, such as the quality of the follicular environment, follicle size, morphology of the cumulus-oocyte complex, and maturation conditions (DE BEM et al, 2014;SOARES et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In another model, brilliant cresyl blue (BCB) stain was widely used to characterize oocytes based on their potential developmental capacity (Catalá et al, ; Salviano, Collares, Becker, Rodrigues, & Rodrigues, ). Recently, Liu et al () used single‐cell RNAseq technology to analyze the transcriptome profiles of porcine oocytes categorized by the BCB stain. A total of 155 genes related to oocyte meiosis, cell cycle, tight junction, and metabolic pathways were differentially expressed between BCB‐negative and BCB‐positive immature germinal vesicle (GV) stage oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The sense sequence of the negative control (NC) was (5′‐3′) UUCUCCGAACGUGUCACGUTT and the antisense sequence was (5′‐3′) ACGUGACACGUUCGGAGAATT. Microinjection of siRNA or antibody into porcine oocytes or 1‐cell embryos was performed using the procedure as described previously (Huan, Xie, Liu, Kong, & Liu, 2015, X. M. Liu et al, 2018a). Briefly, oocytes or embryos in the manipulation medium supplemented with 7.5 μg/ml cytochalasin B and 0.3% bovine serum albumin (BSA) were microinjected with approximately 10 pl siRNA or antibody using sterile femtotips and the FemtoJet express microinjector (Eppendorf).…”
Section: Methodsmentioning
confidence: 99%